The marketing analytics practitioner's guide volume 2 : product, advertising, packaging, biometrics, price and promotion - Charan, Ashok (Singapore : World Scientific Publishing Co. Pte. Ltd., 2024)
"As the use of analytics becomes increasingly important in today's business landscape, The Marketing Analytics Practitioner's Guide (MAPG) provides a thorough understanding of marketing management concepts and their practical applications, making it a valuable resource for professionals and students alike. The four-volume compendium of MAPG provides an in-depth look at marketing management concepts and their practical applications, equipping readers with the knowledge and skills needed to effectively inform daily marketing decisions and strategy development and implementation. It seamlessly blends the art and science of marketing, reflecting the discipline's evolution in the era of data analytics. Whether you're a seasoned marketer or new to the field, the MAPG is an essential guide for mastering the use of analytics in modern marketing practices. Volume II, Parts III to V, is dedicated to Product, Advertising, Packaging, Biometrics, Price, and Promotion. Part III focuses on the product development process, covering the analytic methods and procedures used to screen ideas, concepts, and products during development, launch, and post-launch. Part IV delves into advertising, packaging, and biometrics. The fundamentals, concepts, and core themes of advertising are covered in a chapter that explains how advertising works and what makes it effective and impactful. The chapter on Advertising Analytics focuses on audience engagement, both behavioural and attitudinal, and the analytic techniques and research processes used to test and track advertising. The chapter on packaging is devoted to the analytics and research techniques employed throughout the stages of packaging development and the chapter on biometrics covers biometric techniques and the relevant technologies, devices, metrics, and applications of these techniques that are useful to practitioners. Finally, Part V deals with price and promotion, covering a variety of pricing research methods and techniques for promotions evaluation. This will help the reader to gain an understanding of the importance and application of pricing and promotions in marketing strategy"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Product management; Advertising; Pricing; Marketing -- Management